A Case of Pelvic Inflammatory Disease with Atypic Clinical - Türkmen, Nursel; Eren, Bülent; Fedakar, Recep; Akan, Okan; Saka, Esra (The Bulletin of Legal Medicine, 2004)
Pelvic inflamatory disease (PID) should be investigated on the aspect of clinically and medicolegally, since in clinical practice delayed diagnosis of these cases expose serious morbidity and mortahty problems. In this study we aimed to underline complications and silent clinical course of PID case with literature review. Our case was 38 years old woman died in hospital where was treated for her nonspesific chronic hypocondriac and lumbar pain with antiflamatuary agents. Family history showed that victim had multiple sexual partners. On external examination there was yellow green colored bruise on right outer lateral and left inner aspects of inguinal region. On macroscopic examination lung congestion grayish green membranes in perisplenic and perihepatic areas, fibrous thickening of hepatic and splenic capsules, tuboovarian abses formation, yellowish fluid collection in Douglas pouch and tuba. On microscopic evaluation cardiac congestion, lung hyperemia, liver fibrosis, paranchymal cell, bridging necroses, lymphositic infiltration with follicle formation on tuba uterina wall and omentum. In toxicologic study no substance was detected. Finally death was declared as hepatitis, pelvic abses formation and peritonitis due to pelvic inflamatory disease. Key words: Pelvic inflamatory disease, death, autopsy.
Keywords: pelvic inflamatory disease; death; autopsy